2022
DOI: 10.1007/s12032-021-01636-1
|View full text |Cite
|
Sign up to set email alerts
|

CDK9 inhibitors in multiple myeloma: a review of progress and perspectives

Abstract: Currently, multiple myeloma is not yet considered a curable disease. Despite the recent advances in therapy, the average patient lifespan is still unsatisfactory. Recently, CDK9 inhibitors emerged as a suitable agent to overcome resistance and prolong survival in patients with poor diagnoses. Downregulation of c-MYC, XIAP, Mcl-1 and restoration of p53 tumor-suppressive functions seems to play a key role in achieving clinical response. The applicability of the first generation of CDK9 inhibitors was limited due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…It is well-known that CDK9 plays a main role in the control of basal gene transcription, thus assuring cell transcriptional homeostasis [49]. Previous studies have shown that CDK9 inhibition negatively regulates MYC as well as MCL-1 and BCL-2 expression [50,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that CDK9 plays a main role in the control of basal gene transcription, thus assuring cell transcriptional homeostasis [49]. Previous studies have shown that CDK9 inhibition negatively regulates MYC as well as MCL-1 and BCL-2 expression [50,66].…”
Section: Discussionmentioning
confidence: 99%
“…CDK9 activity regulates mRNA transcription [46,49,50]. When CDK9 activity is inhibited by dinaciclib, protein turnover of short-life cell proteins such as MCL-1 is impaired.…”
Section: Cdk9 Inhibition Mediates Synergy Of Dinaciclib-based Combina...mentioning
confidence: 99%
“…Early attempts to inhibit CDK9 induced loss of fitness in normal as well as cancer cells because of its essentiality across multiple lineages . This on-target toxicity was further compounded by the combination of inadequate pharmacokinetics, target selectivity, and/or efficacy displayed by the first generation of CDK9 inhibitors. ,,, Notably, these CDK9 inhibitors had high affinity for other cyclin-dependent kinases. Engineering selectivity for kinases can often prove challenging given the conservative nature of the ATP binding cleft, a critical region for many kinase-directed drugs.…”
Section: Path To the Clinic: Progress And Challengesmentioning
confidence: 99%
“…The cyclin-dependent kinase 9 (CDK9) is a transcriptional kinase that has attracted recent interest as a clinically relevant target. Given its role as a global regulator of transcription and a critical node in multiple oncogenic transcriptional networks, CDK9 is viewed as an actionable target in a variety of transcriptionally addicted cancers, including many tumors with amplified or overexpressed MYC levels. The biology of CDK9, its role in transcription regulation and cancer, and efforts to discover suitable inhibitors have already been the subject of extensive reviews. Here, we offer a brief review of key consequential aspects of its biochemical networks and explore the progress made in the clinical evaluation of highly selective and novel agents in oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of CDK9 molecules form heterodimers with Cyclin T1, which is also called positive transcription elongation factor b (p-TEFb) that is required for the phosphorylation of the RNA polymerase II (RNA Pol II) C-terminal domain (CTD) and transcription elongation. While the remaining 20% form complexes with Cyclin T2A, Cyclin T2B, or Cyclin K. CDK9 expression has been found to be dysregulated in various types of cancer. Inhibition of CDK9 results in transient transcriptional suppression and preferential depletion of apoptosis-related proteins with short half-lives, such as Mcl-1, c-Myc, and XIAP. So far, several selective CDK9 inhibitors have entered clinical research successively for the treatment of malignant hematological tumors such as acute myeloid leukemia (AML), including AZD4573, VIP152, KB-0742, et al (Figure ), and most of the design concepts of CDK9 inhibitors are focused on CDK subtype selectivity and properties suitable for achieving short target engagement. , Recent studies have shown that MYC gene mutations and abnormal Mcl-1 expression are also one of the main factors driving the onset and metastasis of CRC in addition to malignant hematological tumors. Therefore, targeting CDK9 might work as an appealing strategy for treating CRC.…”
Section: Introductionmentioning
confidence: 99%